MSB Steganography Text Message Insertion Technique On Imagery With Otp And RSA Algorithms - Resti Afrelia Sibuea; Akim M.H. Pardede; Katen Lumbanbatu (International Journal of Health Engineering and Technology, 2022)
The use of image media information has several weaknesses, one of which is that it is easy to be manipulated by certain parties with the help of currently developing technology. Efforts that can be made in increasing the security of sending image information are cryptography, which is the science and art of maintaining message security. In this study, the OTP, RSA and MSB (Most Significant Bit) steganography methods were applied which aim to obtain a stronger cipher by inserting a message into the image so that it is difficult to tap. OTP and RSA algorithms for encrypting and decrypting, MSB (Most Significant Bit) Steganography which is used for encoding and decoding images. The results of this study indicate that by applying the OTP, RSA and MSB (Most Significant Bit) Steganography algorithms can secure messages that are inserted into the image and secure the key for data needs. The encoding and decoding process time is affected by the number of messages to be kept secret.